How Main Stock Exchange Indices React to Covid-19 Pandemic: Daily Evidence from East Asian Countries - Kartal, Mustafa Tevfik; Kilic Depren, Serpil; Depren, Ozer (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2021)
This study investigates whether the Covid-19 and the financial indicators affect the main stock exchange indices of East Asian countries. Number of cases and deaths caused by Covid-19, uncertainty, volatility, foreign exchanges, and mobility are examined by using Quantile Regression and comparing the pre-pandemic and the pandemic periods. The results shows that (i) the indicators have a significant negative impact as expected; (ii) the impact of mobility and pandemic indicators has significance in the trend of the indices whereas they differentiate among countries; (iii) the impact of the variables is significantly differentiated from the low level to the high level.
Keywords: Covid-19 pandemic; East Asian countries; main stock exchange indices; quantile regression; Business & Economics